Chapter The Mountain Village of Razëm - Laurìa, Antonio (Studi e saggi, 2020)
Part II of the book focusses on Razëm, a hamlet of the mountain village of Vrith, in the Municipality of Malësi e Madhe. Razëm lies within the Regional Natural Park of Shkrel and is considered the "gateway" to the Western Albanian Alps. The evocative landscape, the quality of the air and the proximity to Shkodër have transformed Razëm into a proper tourist resort. In the first chapters, the importance of the intangible heritage is stressed. The quality of the typical products and of the culinary tradition, the rhapsodic chants based on the Eposi i Kreshnikëve, the tradition of the customary law based on the Kanun code, the religious festivities and the xhubleta (as a most significant feature of local craftsmanship) are some of the issues addressed. In the following chapters, the multiple aspects of the tangible heritage are analysed. Here, the quality of the natural and pastoral landscape - characterised by alpine pastures and typical hut settlements -, together with the building tradition of the area, is highlighted. A special attention is dedicated to a complex of villas built by the rich bourgeoisie from Shkodër during the Twenties and Thirties, a unique phenomenon that deserves a proper in-depth study. For each of the aforementioned issues, the theoretical and historical analysis are closely bound to an evaluation of those features of the cultural heritage that could be enhanced to guarantee a sustainable tourism development of the area. Each chapter ends with a consistent set of specific intervention strategies. They are substantive tools for action aimed at public and private local actors.